Chromophore-labelled, luminescent platinum complexes: syntheses, structures, and spectroscopic properties. Issue 25 (31st May 2016) - Stacey, Oliver J.; Ward, Benjamin D.; Coles, Simon J.; Horton, Peter N.; Pope, Simon J. A.
Abstract : Ligands based upon 4-carboxamide-2-phenylquinoline have been functionalised with naphthyl, anthracenyl and pyrenyl chromophores. The pyrene appended Pt(ii ) complex shows excited state equilibration and a long emission lifetime. Abstract : Ligands based upon 4-carboxamide-2-phenylquinoline derivatives have been synthesised with solubilising octyl hydrocarbon chains and tethered aromatic chromophores to give naphthyl (HL 2 ), anthracenyl (HL 3 ) and pyrenyl (HL 4 ) ligand variants, together with a non-chromophoric analogue (HL 1 ) for comparison. 1 H NMR spectroscopic studies of the ligands showed that two non-interchangeable isomers exist forHL 2 andHL 4 while only one isomer exists forHL 1 andHL 3 . Supporting DFT calculations onHL 4 suggest that the two isomers may be closely isoenergetic with a relatively high barrier to exchange of ca. 100 kJ mol −1 . These new ligands were cyclometalated with Pt(ii ) to give complexes [Pt(L 1–4 )(acac)] (acac = acetylacetonate). The spectroscopically characterised complexes were studied using multinuclear NMR spectroscopy including 195 Pt{ 1 H} NMR studies which revealed δ Pt ca . −2785 ppm for [Pt(L 1–4 )(acac)]. X-ray crystallographic studies were undertaken on [Pt(L 3 )(acac)] and [Pt(L 4 )(acac)], each showing the weakly distorted square planar geometry at Pt(ii ); the structure of [Pt(L 3 )(acac)] showed evidence for intermolecular Pt–Pt interactions. The UV-vis. absorption studies show that the spectral profiles for [Pt(L 2–4 )(acac)] are a composite of the organic chromophore centred bands and a broad 1 MLCT (5d → π*) band ( ca. 440 nm) associated with the complex. Luminescence studies showed that complexes [Pt(L 2–4 )(acac)] are dual emissive with fluorescence characteristic of the tethered fluorophore and long-lived phosphorescence attributed to 3 MLCT emission. In the case of the pyrenyl derivative, [Pt(L 4 )(acac)], the close energetic matching of the 3 MLCT and 3 LCpyr excited states led to an elongation of the 3 MLCT emission lifetime ( τ = 42 μs) under degassed solvent conditions, suggestive of energy transfer processes between the two states.